The Active Compound Thymoquinone Alters Chondrogenic Differentiation of Human Mesenchymal Stem Cells via Modulation of Intracellular Signaling - Banu ISKENDER (Medeniyet Medical Journal)
Objective: The regenerative potential of mesenchymal stem cell (MSC)-like cells in the cartilage is relatively low because of the lack of innervation and vascularization. The increase in proinflammatory cytokines in cartilage damage can increase the expression of apoptotic and proinflammatory genes and the matrix degradation enzymes via nuclear factor-κB (NF-κB). Previous evidence suggested that thymoquinone (TQ) suppresses tumor necrosis factor-α-mediated NF-κB activation in different cancer cell lines. The suppression of the NF-κB pathway increases chondrogenic differentiation by inhibiting osteogenic differentiation in MSCs. Therefore, the current descriptive study aimed at highlighting the role of thymoquinone on the differentiation of human MSCs (hMSCs) since it is predicted that agents with known anti-inflammatory properties such as TQ have the potential to alter the chondrogenic differentiation of MSCs. Methods: In this study, the bioactive component thymoquinone, with its well-documented effects on the NF-κB signaling pathway, was used in hMSC differentiation assays. The effects of thymoquinone on hMSC differentiation and the relevant intracellular signaling pathways were determined using immunocytochemistry and western blotting for the first time. Changes in the phosphorylation status of some signaling components involved in NF-κB and mTOR signaling were also evaluated. Results: The chondrogenic differentiation potential of hMSCs treated with TQ decreased, concomitant with the decrease in the activity of NF-κB signaling pathway components. Thymoquinone triggered the suppression of NF-κB signaling, which interfered with the chondrogenic potential of hMSC, as opposed to some previous findings in the literature. Conclusions: The results of this study are of great importance for the optimization of directed differentiation of hMSCs and hMSC-mediated cellular therapies.